PENGARUH PENERAPAN METODE OUTDOOR LEARNING BERBASIS KELOMPOK TERHADAP HASIL BELAJAR IPS DI SDN - Karmila Karmila (Universitas Negeri Makassar, 2016)
Purpose of this study were (i) How does outdoor learning methods overview of the application of the group based on the results of the fourth grade social studies at the Teachers' Training College Maccini SDN Makassar (ii) Is there any influence of outdoor learning method based on learning outcomes IPS group of fourth grade in SDN KIP Maccini Makassar. This research is a quantitative type of true experimental research. Techniques of collecting data through tests of student learning outcomes. The population in this study is the fourth grade students of the school year 2014/2015 The samples in this study were taken from two schools dikecamatan Makassar SDN KIP Maccini and SD Instruction Maccini ie the whole fourth grade students numbered seventy people from the large number of the population. The result showed that (i) description of the application of methods of outdoor learning group based on the results of social studies class IV in SDN Teachers' Training College Maccini Makassar (ii) There is the effect of the application of methods of outdoor learning group based on learning outcomes IPS fourth grade students at SDN KIP Maccini Makassar.